Anxiety Severity, Perceived Risk of COVID-19 and Individual Functioning in Emerging Adults Facing the Pandemic - Germani, Alessandro; Buratta, Livia; Delvecchio, Elisa; Gizzi, Giulia; Mazzeschi, Claudia (Frontiers in Psychology, 2020)
COVID-19 is showing a strong impact on population in terms of uncertainty and instability in different areas of the daily life. Uncertainty and instability per se characterize the emerging adulthood (EA), they generate worries for the present and the future and they are source of anxiety, which impacts negatively on personal and interpersonal functioning. Anxiety seems a central affect during the pandemic and recent studies suggested that it is linked to COVID-19 risk perception. A sample of 1045 Italian emerging adults was collected aimed: (1) to assess anxiety severity and perceived risk related to COVID-19 and their association; (2) to compare general health and protective factors such as secure attitude in relationship, self-esteem, and self-efficacy across anxiety severity and perceived risk categories. Findings highlighted that anxiety severity categories were distributed homogeneously across the sample and that half of participants referred moderate-severe anxiety. A series of ANOVAs and post-hoc comparisons showed that general health and all protective factors decreased according to anxiety severity. Also, they were higher in participants with high perceived risk, with the exception of self-efficacy. Given the challenging features of the pandemic and EA, it is crucial to monitor anxiety severity in order to prevent last longing effects on mental and physical health, as well as keeping emerging adults informed about the risks related to the pandemic. At last, intervention and supportive programs based on improving self-esteem, self-efficacy, and confidence in relationships, should be offered to emerging adults over the long term, far beyond the current outbreak.